Rights and Obligations of Persons with Intellectual Disabilities as Perpetrators of Criminal Acts - Yana, Tri (Resolusi: Jurnal Sosial Politik, 2024)
In criminal law, an act is a fundamental element in determining a criminal offense. Often described as strafbaar feit or a punishable act, criminal behavior can be committed by any individual. Although people with special conditions, such as intellectual disabilities, have a lower incidence of committing crimes, this does not negate the possibility of their involvement in criminal acts. Individuals with intellectual disabilities are recognized as human beings with both rights and obligations. However, under criminal law, certain individuals with disabilities may receive special consideration through the protection of Article 44 of the Indonesian Criminal Code (KUHP). This has led to a debate regarding the legal status of persons with disabilities: should they be held responsible for their actions as perpetrators of crimes, or should they be protected as individuals with special needs whose rights must be safeguarded? Psychiatric Forensic Evaluation (Visum et Repertum Psikiatri or VeR Psikiatri) plays a critical role in legal decisions concerning the mental condition of individuals with intellectual disabilities who have committed criminal offenses. This research, focusing on a case study from the Wonosobo District Court (Case No. 16/Pid.Sus/2019/PN.Wsb), employs a qualitative research approach, analyzed juridically and normatively. The research is based on a review of legal literature and interviews with relevant authorities.